Regional Determinants of Efficiency Growth of Small and Medium-Sized Enterprises. Evidence from Poland - Teresa Łuczka; Paweł Przepióra (Journal of Entrepreneurship, Management and Innovation)

(untitled)
SMEs sector plays a vital role in modern economies. Therefore, the interest in its functioning among economists is in fact quite natural. This article is a part of a current research on regional factors contributing to the development of enterprises in this category. The first section examines earlier studies in this field conducted globally and in Poland. According to them, many elements enable the SME’s development. It is not surprisingly that the specified set of pro-growth factors does not exists. Next section describes the results of the author’s own studies in the fields. These studies relate to regional factors contributing to the efficiency growth of micro, small and medium-sized enterprises in Poland. Data used in the study was collected from GUS[1] and EUROSTAT and encompassed 16 provinces for the years 2003-2008. The model prepared included 11 independent variables on labor force, social mobility, living standard and R&D policy. The authors would have gladly considered more than 11 explanatory variable, but the inaccessibility of such data made it impossible. In the next step, using GRETL software, equations of regression were defined. On this basis it was concluded that the most important factors contributing to efficiency growth of SMEs are the amount of spending on R&D and the level of wages.